Spatio-temporal variation of biogenic volatile organic compounds emissions in China - Li, LY; Y. Chen; Xie, S. D. (Environmental pollution, 2013)
Aiming to reduce the large uncertainties of biogenic volatile organic compounds (BVOCs) emissions estimation, the emission inventory of BVOCs in China at a high spatial and temporal resolution of 36 km × 36 km and 1 h was established using MEGANv2.1 with MM5 providing high-resolution meteorological data, based on the most detailed and latest vegetation investigations. BVOC emissions from 82 plant functional types in China were computed firstly. More local species-specific emission rates were developed combining statistical analysis and category classification, and the leaf biomass was estimated based on vegetation volume and production with biomass-apportion models. The total annual BVOC emissions in 2003 were 42.5 Tg, including isoprene 23.4 Tg, monoterpene 5.6 Tg, sesquiterpene 1.0 Tg, and other VOCs (OVOCs) 12.5 Tg. Subtropical and tropical evergreen and deciduous broadleaf shrubs, Quercus, and bamboo contributed more than 45% to the total BVOC emissions. The highest biogenic emissions were found over northeastern, southeastern, and southwestern China. Strong seasonal pattern was observed with the highest BVOC emissions in July and the lowest in January and December, with daily emission peaked at approximately 13:00 or 14:00 local time.